Second Language Writing Anxiety of Indonesian EFL Students - Reni Kusumaningputri; Tri Ayu Ningsih; Wisasongko Wisasongko (Lingua Cultura, 2018)
This research reported the types, as well as the causal factors of writing anxiety experienced by 44 volunteered Indonesian student writers from the first and second year of college. This research applied two questionnaires to get descriptions of types and causal factors of writing anxiety; Second Language Writing Anxiety Inventory (SLWAI) and Causes of Writing Anxiety Inventory (CWAI), and interview. The findings show that cognitive anxiety is found to be the most experienced type of writing anxiety among both students’ levels. There is a slight difference in the result of CWAI questionnaire in that three major causal factors of freshmen writing anxiety are language difficulties, time pressure, and insufficient writing practice. Meanwhile, the causal factors of sophomores are insufficient writing practice, language difficulties, and insufficient writing technique. These suggest that classroom instructions need to gear on improving students’ linguistic capabilities and writing techniques through modeling.